2009
DOI: 10.1159/000235827
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Models in Predicting Topical Antifungal Efficacy: Practical Aspects and Challenges

Abstract: What are efficient screening models for improved topical antifungals? The use of minimum inhibitory concentrations (MICs) as one such parameter is discussed; we focus on the use of animal membranes for in vitro testing while highlighting the pros and cons of each model, exploring alternatives and discussing the importance of data transferability to humans and the influence of penetration kinetics in topical antifungal efficacy. Ultimately, the gold standard of testing is in vivo in humans; however, initiating … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 102 publications
(58 reference statements)
0
4
0
1
Order By: Relevance
“…Measurement of dermal absorption for the purpose of targeted skin delivery, systemic delivery, or toxicological assessment should be done under the correct conditions, ideally using the gold-standard experimental model: in vivo human skin. 13 However, this is not always possible, due to the high cost of human trials and concerns over applying substances or materials with potentially toxic effects. As well, in vivo responses may be difficult to measure and interpret and subject to significant variability.…”
Section: Models Used To Evaluate Dermal Absorptionmentioning
confidence: 99%
“…Measurement of dermal absorption for the purpose of targeted skin delivery, systemic delivery, or toxicological assessment should be done under the correct conditions, ideally using the gold-standard experimental model: in vivo human skin. 13 However, this is not always possible, due to the high cost of human trials and concerns over applying substances or materials with potentially toxic effects. As well, in vivo responses may be difficult to measure and interpret and subject to significant variability.…”
Section: Models Used To Evaluate Dermal Absorptionmentioning
confidence: 99%
“…Ex vivo permeation studies using human skin and under suitable conditions are successfully used to predict in vivo behavior of topical formulations [54,55]. The results of this assay revealed that APR-ME could be used as an effective local treatment for skin inflammation since the drug was able to cross the SC and remain retained into the skin (479.35 ± 102.85 µg APR/g skin/cm 2 ) without reaching the receptor compartment.…”
Section: Discussionmentioning
confidence: 99%
“…), application (finite or infinite dose? ), and temperature 50 . In 1989, Aly et al carried out three phases of research for topical antifungal, first by research pig skin and human body skin in side‐by‐side comparison and by demonstrating that cyclopyroxolamine 1 percent, in two separate vehicles, lotion, and cream, similarly penetrated all stratum corneum layers in both skin types and inhibited the growth of T. mentagrophytes and Candida albicans 50,51 …”
Section: Classification Of Methodsmentioning
confidence: 99%